Analysis of query execution speed in the selected NoSQL databases - Wojciech Bolesta (Journal of Computer Sciences Institute, 2018)
The scientific article deals with a comparison of the query speed of two NoSQL databases. Described databases will be MongoDB and CouchDB. The work presents speed comparisons of such queries as adding data to the database, editing database data, deleting data from the database, and searching data in the database. Also a general comparison of bases will be presented, with the answer to the question of which of the tested NoSQL databases is faster.